2017
DOI: 10.1002/icd.2026
|View full text |Cite
|
Sign up to set email alerts
|

Associations of sleep problems with externalizing behaviors and preacademic performance: The moderating role of family socioeconomic status

Abstract: Previous research has tended to measure sleep problems as an aggregated construct and neglected the potential moderating role of family socioeconomic status (SES). Also, most research has been conducted with school‐aged children and adolescents from European and European–American families. This study filled some of these gaps in the literature by examining whether family SES moderated the associations of bedtime resistance, parasomnia, and disordered breathing with externalizing behaviors and preacademic perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…For cognitive quality, the negative effect of PAS was significant across different levels of family SES, but the effect decreased as family SES increased. These results are consistent with existing studies that found a compensatory role of the economic advantage of high family SES (Duan et al, 2018; Lam & Chung, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For cognitive quality, the negative effect of PAS was significant across different levels of family SES, but the effect decreased as family SES increased. These results are consistent with existing studies that found a compensatory role of the economic advantage of high family SES (Duan et al, 2018; Lam & Chung, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…For example, studies found that parental involvement had a stronger positive association with academic behaviors among low-SES families than among high-SES families (Duan et al, 2018). Another study on preschool children found that bedtime resistance was positively related to behavioral problems and negatively related to academic performance only among low-SES families but not significantly among high-SES families (Lam & Chung, 2017). The two studies imply that high SES may compensate for the negative role of low parental involvement and poor sleep quality.…”
Section: Introductionmentioning
confidence: 99%
“…Child pre-academic ability was assessed using a 4-item measure ( Lam & Chung, 2017 ). On a 5-point scale ranging from 1 ( Very Poor ) to 5 ( Very Good ), mothers rated their children’s Chinese, English, Math, and general learning ability (e.g., “This child’s Chinese ability is…”).…”
Section: Methodsmentioning
confidence: 99%
“…Research on children’s and adolescents’ social development has been largely focused on problem behaviors, including externalizing and internalizing problem behaviors [ 1 , 2 , 3 ]. It is shown that externalizing problem behaviors, such as aggressive, hyperactive, and disruptive behaviors, positively predict peer rejection and low academic performance [ 4 , 5 ]. Similarly, it has also been found that internalizing problem behaviors (e.g., anxiety, depression) positively predict sleep problems and peer victimization [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%